How does the ultrasonic assist CO2 immiscible flooding? - Hengli Wang; Leng Tian; Yanzhong Zhen; Yating Li; Yi Gao; Gaorun Zhong; Kaiqiang Zhang (Ultrasonics Sonochemistry)
CO2 flooding is considered one of the most important methods for reducing CO2 emissions and increasing oil production from reservoirs. However, the challenges of low recovery rates and poor economic benefits in CO2 immiscible flooding significantly hinder its widespread application. To address these issues, this paper proposes the use of ultrasonic-assisted CO2 immiscible flooding to enhance oil recovery (EOR) and analyzes its underlying mechanisms. First, the distribution characteristics of residual oil in CO2 immiscible flooding were examined using high pressure mercury injection (HPMI), nuclear magnetic resonance (NMR), and microscopic visualization displacement (MVD) experiments. Next, the changes in oil recovery and residual oil distribution after applying ultrasonic-assisted CO2 immiscible flooding were analyzed. Finally, the mechanism of EOR through ultrasonic-assisted CO2 immiscible flooding was summarized based on the results of interfacial tension (IFT) tests. The findings indicate that the recovery rate of CO2 immiscible flooding without ultrasound is 53.33 %, with residual oil primarily distributed in the form of films and flakes within the pores. The ultrasonic assisted CO2 immiscible flooding with frequency of 28 KHz and power of 200 W was provided by ultrasonic horn, and the recovery rate increased by 62.84 % after 60 min. With ultrasonic assistance, the recovery rate increased to 62.84 %, and the maximum radius of residual oil droplets was reduced from 81.8 μm to 36.5 μm. Additionally, the amount of residual oil in the 0.1 μm to 1 μm range slightly decreased, suggesting that ultrasonic assistance mainly improves the recovery of flake residual oil, with a slight improvement in film residual oil recovery as well. Ultrasound can enlarge the pore and throat radius and reduce the interfacial tension in the CO2-oil system, allowing more flake residual oil to be displaced. Moreover, the high-frequency vibrations of the ultrasound can reduce the thickness of the oil film, enhancing the recovery of film residual oil. This study supports the further application of ultrasonic-assisted CO2 immiscible flooding in both scientific research and engineering practice.